2010
DOI: 10.1007/s00705-010-0695-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of porcine enteric caliciviruses in pigs raised in Rio de Janeiro State, Brazil

Abstract: Porcine enteric caliciviruses (PEC) belong to the genera Norovirus and Sapovirus within the family Caliciviridae. They are enteric pathogens and are considered potential zoonotic agents. In this study, the circulation of PEC was evaluated by RT-PCR of stool samples and intestinal contents of pigs raised in Rio de Janeiro State, Brazil. Both porcine norovirus (PoNoV) and porcine sapovirus (PoSaV) were detected. The PoNoV strains were classified as genogroup II, genotypes 11, 18 and 19. The PoSaV strains were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 96%
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 96%
“…Molecular diagnostics performed in different countries have established a worldwide distribution of NoV in pigproduction systems (Wolf et al 2009;Keum et al 2009;L'Homme et al 2009;Mijovski et al 2010;Cunha et al 2010a). In general, the reported rates of PoNoV detection were low, ranging from 0 to 2 % (Martínez et al 2006;Keum et al 2009;Mijovski et al 2010) to 20 % (Wang et al 2006b).…”
Section: Resultsmentioning
confidence: 93%
“…Cunha et al (2010a) reported 8 % (20/261) of PoNoV detection rate in finisher pigs in Rio de Janeiro state, Brazil. A possible explanation for this significant difference between the frequencies of NoV in pigs in the same country is the RT-PCR sensitivity, which can be higher when using specific primers for PoNoV detection.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Emerging viral infections of pigs have been recently reported in Brazil; these include infections due to rotaviruses B and C (Médici et al 2011), caliciviruses (Barry et al 2008, Cunha et al 2010, kobuvirus , and hepatitis E virus (Gardinali et al 2012). The associations of these emerging viruses and of TTSuV with disease in pigs have not been elucidated (Meng 2012).…”
Section: Discussionmentioning
confidence: 99%